Exome sequencing reveals riboflavin transporter mutations as a cause of motor neuron disease - Johnson, Janel O; Gibbs, J Raphael; Megarbane, Andre; Urtizberea, J Andoni; Hernandez, Dena G; Foley, A Reghan; Arepalli, Sampath; Pandraud, Amelie; Simón-Sánchez, Javier; Clayton, Peter; Reilly, Mary M; Muntoni, Francesco; et al. (Brain (London, England : 1878), 2012)
Brown-Vialetto-Van Laere syndrome was first described in 1894 as a rare neurodegenerative disorder characterized by progressive sensorineural deafness in combination with childhood amyotrophic lateral sclerosis. Mutations in the gene, SLC52A3 (formerly C20orf54), one of three known riboflavin transporter genes, have recently been shown to underlie a number of severe cases of Brown-Vialetto-Van Laere syndrome; however, cases and families with this disease exist that do not appear to be caused by SLC52A3 mutations. We used a combination of linkage and exome sequencing to identify the disease causing mutation in an extended Lebanese Brown-Vialetto-Van Laere kindred, whose affected members were negative for SLC52A3 mutations. We identified a novel mutation in a second member of the riboflavin transporter gene family (gene symbol: SLC52A2) as the cause of disease in this family. The same mutation was identified in one additional subject, from 44 screened. Within this group of 44 patients, we also identified two additional cases with SLC52A3 mutations, but none with mutations in the remaining member of this gene family, SLC52A1. We believe this strongly supports the notion that defective riboflavin transport plays an important role in Brown-Vialetto-Van Laere syndrome. Initial work has indicated that patients with SLC52A3 defects respond to riboflavin treatment clinically and biochemically. Clearly, this makes an excellent candidate therapy for the SLC52A2 mutation-positive patients identified here. Initial riboflavin treatment of one of these patients shows promising results.